A coupled thermomechanical crystal plasticity model applied to Quenched and Partitioned steel. (October 2020) - Connolly, Daniel S.; Kohar, Christopher P.; Muhammad, Waqas; Hector, Louis G.; Mishra, Raja K.; Inal, Kaan
Abstract: Quenched and Partitioned (QP) steel is a class of Advanced High Strength Steel (AHSS) that exhibits high strength and good ductility. These desirable properties are a consequence of the Transformation Induced Plasticity (TRIP) effect where retained austenite transforms into martensite under applied stress and strain. Accurate microstructural modeling of these advanced deformation mechanisms is critical for automakers to exploit QP steels for automotive weight reduction applications. In this work, the stress and martensitic transformation response of a QP1180 steel alloy are characterized using in-situ High Energy X-Ray Diffraction (HEXRD) uniaxial tension experiments. The initial microstructure is characterized using Electron Backscatter Diffraction (EBSD) and Scanning Electron Microscope (SEM) data. A novel thermodynamically consistent rate-dependent crystal plasticity formulation is used to simulate the large deformation behavior of QP steels that exhibit the TRIP effect. The TRIP effect is captured through a martensite variant selection and evolution scheme, which is governed by a driving force that accounts for various effects (i.e., temperature, orientation, hydrostatic pressure, and martensite surface energy). The constitutive model is implemented into a thermo-mechanical Crystal Plasticity (CP) Finite Element Method (FEM) formulation to study the effect of texture, phase morphology and temperature on the bulk material properties of QP1180 steel. A new method for incorporating thermal boundary conditions in CPFEM models is proposed. The constitutive model is calibrated using experimental stress-strain and martensite evolution measurements. Significant variance in transformation rate was observed, consistent with preferential transformation in the ⟨ 100 ⟩ crystal direction. Numerical experiments are conducted to study the effect of thermal and mechanical boundary conditions. Significant differences are observed between the simulations of interrupted and non-interrupted uniaxial tension as a result of the differences in the evolution of temperature. Additional numerical experiments were conducted that demonstrate the fidelity of the constitutive model for elevated temperatures and strain-rates, for several thermal boundary conditions. These simulations showed that the predicted RA and temperature evolution behaviors under quasi-static deformation were not accurately captured, either with adiabatic or isothermal boundary conditions. Finally, simulations showed that the RA and temperature evolution behavior under moderate strain-rates are accurately captured by adiabatic boundary conditions. Highlights: Experimental characterization of QP1180 steel. A novel thermodynamically consistent rate-dependent crystal plasticity model. A novel method for incorporating thermal boundary conditions into representative volume elements. Highlights the significance in accounting for interrupted test conditions for model calibration. Numerical experiments demonstrate model fidelity for elevated temperatures and strain-rates.